2006
DOI: 10.1080/14616730600856149
|View full text |Cite
|
Sign up to set email alerts
|

Maternal secure-base scripts and children’s attachment security in an adopted sample

Abstract: Studies of families with adopted children are of special interest to attachment theorists because they afford opportunities to probe assumptions of attachment theory with regard to the developmental timing of interactions necessary to form primary attachments and also with regard to effects of shared genes on child attachment quality. In Bowlby's model, attachment-relevant behaviors and interactions are observable from the moment of birth, but for adoptive families, these interactions cannot begin until the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
1
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 32 publications
2
43
1
5
Order By: Relevance
“…In our data, secure base scriptedness in parent narratives predicted the child's attachment security as characterized by the Attachment Q-set. These results are consistent with a large literature relating adult attachment organization to child attachment security (van IJzendoorn, 1995) and serves as additional evidence (see also Vaughn et al, 2007;Verı´ssimo & Salvaterra, 2006) for the validity of the Attachment Script Representation measure. As with Steele et al, we found that child attachment security was similar across parents and we attempted to probe the sources of this dependency.…”
Section: Psychometric and Cross-parent Comparisonssupporting
confidence: 81%
See 2 more Smart Citations
“…In our data, secure base scriptedness in parent narratives predicted the child's attachment security as characterized by the Attachment Q-set. These results are consistent with a large literature relating adult attachment organization to child attachment security (van IJzendoorn, 1995) and serves as additional evidence (see also Vaughn et al, 2007;Verı´ssimo & Salvaterra, 2006) for the validity of the Attachment Script Representation measure. As with Steele et al, we found that child attachment security was similar across parents and we attempted to probe the sources of this dependency.…”
Section: Psychometric and Cross-parent Comparisonssupporting
confidence: 81%
“…Because no data for the Attachment Script Representation (Waters & RodriguesDoolabh, 2004) have been published to date for fathers, our data served as an opportunity to explore the psychometric attributes of this measure with a sample of fathers and to examine whether the instrument is used by fathers in the same manner that we have found it used by mothers (e.g., Vaughn et al, 2007;Verı´ssimo & Salvaterra, 2006). The data also afford the opportunity to consider previously reported findings regarding similarities of child attachment assessments across parents (i.e., Steele et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Profundizar en estas cuestiones en el contexto "natural" de la adopción permite contar con un entorno único para abordar el efecto de las variables ambientales antes y después de la adopción (Palacios, Román, Moreno y León, 2009;Palacios, Sánchez-Sandoval y León, 2005;Veríssimo y Salvaterra, 2006;Rutter, 2005; entre otros). En este sentido, explorar el papel que juega el nuevo contexto de crianza en la recuperación y ajuste de los niños adoptados adquiere una gran relevancia en el ámbito de la psicología evolutiva.…”
Section: Introductionunclassified
“…La existencia de este prototipo del guion de base segura ha sido empí-ricamente comprobada en diversos países y contextos (Coppola, Vaughn, Cassibba & Costantini, 2006;Rodrigues-Doolabh, Zevallos, Turan & Green, 2003;Verissimo & Salvaterra, 2006;.…”
unclassified